5 Direct Microscopic Transsphenoidal Surgery with Hybrid Use of Endoscopy (Microsurgical and Endoscopic Approaches to the Skull Base, 2021)
The merits of direct endonasal microscopic transsphenoidal surgery (TSS) with the hybrid use of endoscopy are well recognized in contemporary neurosurgical practice for central skull base lesions. These include: easy and safe direct access to the lesion with no intervening brain tissue, preservation of the integrity of oral and nasal cavity, mitigation of inherent complications of craniotomy, and efficient tumor resection, facilitated by the panoramic view of the endoscope. Variations in TSS approach mirror its temporal evolution over the past 100 years and are credited to several avant-garde pioneers.1,​2,​3,​4,​5 The resurgence of neuroendoscopy6,​7,​8 for solo or hybrid use and the introduction of endonasal extended direct TSS approach enhanced the list of indications for this route to encompass giant pituitary adenomas with extensions into the suprasellar region, medial cavernous sinus, or the clivus, and to include other lesions in this region such as craniopharyngiomas, Rathke’s cyst, dermoid cyst, and select cases of meningiomas or chordomas. This chapter describes the four stages of direct endonasal microscopic TSS approach and refers to the technical aspects of hybrid use of endoscope. The author highlights the important anatomical landmarks for guidance and includes pearls, challenges, and recommendations related to each stage of the intervention.
Keywords: transsphenoidal; microscope; endoscope; pituitary; sellar; approach; tumor